2014
DOI: 10.2106/jbjs.l.01205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Deformity with Respect to the Talus in Patients with Posterior Tibial Tendon Dysfunction and Controls Using Multiplanar Weight-Bearing Imaging or Conventional Radiography

Abstract: Deformity with respect to the talus in posterior tibial tendon dysfunction is multifactorial, but was notably seen at the talonavicular joint in the sagittal plane with both modalities. Good to excellent agreement was found between weight-bearing radiographs and multiplanar weight-bearing images for many parameters; however, a greater number of significant differences was found between the flatfoot and control groups for multiplanar weight-bearing images. This implies a potential role for multiplanar modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 20 publications
3
37
0
2
Order By: Relevance
“…If the medial longitudinal arch is restored to its normal alignment on non-weightbearing radiographs, the flat foot is said to be flexible. 29,[34][35][36] Several lines and angle measurements have been described for the assessment of the foot alignment, and all of them are evaluated on standing radiographs: 4,[35][36][37] • The calcaneal inclination angle is the angle formed by a line tangent to the inferior cortex of the calcaneus and the horizontal plantar plane; it reflects the height of the plantar The orthostatic MRI examination is also useful in the evaluation of the biomechanical changes of the ankle and foot in patients with mid-talar and subtalar joint pathologies. In our experience in the evaluation of patients with traumatic and overload pathologies of the coxa pedis, we found an increase of the alterations of the spring ligament and the sinus tarsi in weight-bearing scans.…”
Section: Weight-bearing Ankle and Footmentioning
confidence: 99%
See 1 more Smart Citation
“…If the medial longitudinal arch is restored to its normal alignment on non-weightbearing radiographs, the flat foot is said to be flexible. 29,[34][35][36] Several lines and angle measurements have been described for the assessment of the foot alignment, and all of them are evaluated on standing radiographs: 4,[35][36][37] • The calcaneal inclination angle is the angle formed by a line tangent to the inferior cortex of the calcaneus and the horizontal plantar plane; it reflects the height of the plantar The orthostatic MRI examination is also useful in the evaluation of the biomechanical changes of the ankle and foot in patients with mid-talar and subtalar joint pathologies. In our experience in the evaluation of patients with traumatic and overload pathologies of the coxa pedis, we found an increase of the alterations of the spring ligament and the sinus tarsi in weight-bearing scans.…”
Section: Weight-bearing Ankle and Footmentioning
confidence: 99%
“…For pes planus, information obtained under physiologic weight-bearing conditions probably better represents changes relevant to surgical planning. 4,29,[35][36][37] The following quantitative parameters are evaluated on this view:…”
Section: Weight-bearing Ankle and Footmentioning
confidence: 99%
“…Thus, the relationship between the distal tibia, talus and calcaneus can be assessed in a more physiological and thus more accurate manner. 46 , 47 The following studies used weight-bearing CT scans to assess hindfoot alignment in the coronal plane: Hirschmann et al 47 found significant changes in weight-bearing or non-weight-bearing CT scans regarding the hindfoot alignment. Burssens et al 48 introduced a novel hindfoot angle in varus and valgus malaligned feet.…”
Section: Radiographic Evaluation Of the Hindfootmentioning
confidence: 99%
“…Deformity Analysis Based on multiplanar weight-bearing imaging, the foot deformity associated with posterior tibial tendon dysfunction primarily involves the talonavicular joint in the sagittal plane 84 . In a case-control study using weight-bearing radiographs, Nosewicz et al noted that varus and valgus talar tilt in the frontal plane did not reliably predict sagittal and horizontal positions.…”
Section: Foot and Ankle Reconstructionmentioning
confidence: 99%